Spectrum of renal disease in scleroderma other than scleroderma renal crisis: A review of the literature - Farrukh, Larabe; Steen, Virginia; Shapiro, Lee; Faddoul, Geovani; Mehta, Swati (Clinical nephrology, 2024)
Systemic sclerosis (SSc) is a multi-system rheumatic disease characterized by vascular and fibrotic manifestations that can affect practically every organ. Scleroderma renal crisis (SRC) is the most common renal manifestation of SSc. However, with the use of angiotensin-converting enzyme inhibitors (ACEi), the morbidity and mortality associated with SRC has significantly reduced. Renal manifestations in SSc other than SRC have been generally under-recognized and can be left untreated, which can lead to grave consequences in this patient population. In this article, we will describe the spectrum of renal disease in SSc besides SRC. A literature search was conducted on PubMed and Cochrane from inception to December 2022 using medical subject headings (MeSH) terms for "scleroderma", "systemic sclerosis" combined with "renal injury", and "renal dysfunction". We included case reports, case series, observational studies, and literature reviews. The initial search revealed 393 articles. After the exclusion of duplicates and non-relevant articles, data was included from 30 articles and 45 patients. The mean age was 55.2 years, 9 males (20%) and 36 females (80%). The most reported renal manifestations included: ANCA-associated vasculitis (n = 22), penicillamine-induced renal injury (n = 8), oxalate nephropathy (n = 5), Goodpasture syndrome (n = 4), nephrotic range proteinuria (n = 2), renal artery stenosis (n = 2), membranous glomerulonephritis (n = 1), and Evans syndrome (n = 1). The spectrum of kidney involvement in SSc can range from asymptomatic reduction of the glomerular filtration rate to life-threatening scleroderma renal crisis. Therefore, it is essential that physicians closely monitor renal function in these patients for any emerging renal dysfunction.